Persuasion knowledge for design community: Design of PToolkit prototype - Saidin, Aeni Zuhana; Macaulay, Catriona; Hine, Nick; Shaari, Nassiriah; Alwi, Asmidah (2013)
Persuasion knowledge has been used in various disciplines, and now is being utilized by interaction designer for designing persuasive application.Although lots of interactive applications were designed with aims to influence on certain aspects the availability of persuasion knowledge for design community is limited.Therefore, Persuasion Knowledge Toolkit (PToolkit) is designed to make the persuasion knowledge more easily accessible for designer during the design ideation phase.This paper describes the design process of PToolkit prototype in making the persuasion knowledge available for designers.